1989
DOI: 10.1172/jci114288
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a novel cholecystokinin (CCK) receptor antagonist, MK-329, on gallbladder contraction and gastric emptying in humans. Implications for the physiology of CCK.

Abstract: To explore the physiology of cholecystokinin (CCK) in humans, we investigated the effect on gallbladder contraction and gastric emptying of a recently developed CCK receptor antagonist, . In a double-blind, four-period crossover study eight subjects received single doses of 0.5, 2, or 10 mg MK-329, or placebo, followed by an intravenous infusion of CCK-8 (30 pmol/kg. h). In placebo-treated subjects gallbladder volumes decreased on average to 43% of initial volumes after 2 h of CCK infusion. MK-329 caused a dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
60
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(69 citation statements)
references
References 19 publications
9
60
0
Order By: Relevance
“…This phenomenon has been observed before with CCK-1 receptor antagonists (6,20,26): the explanations include activation of a negative feedback mechanism due to low concentrations of bile and/or pancreatic juice constituents in the duodenal lumen and interference with autoregulating, inhibitory CCK-1 receptors on the I cell.…”
Section: Discussionsupporting
confidence: 53%
“…This phenomenon has been observed before with CCK-1 receptor antagonists (6,20,26): the explanations include activation of a negative feedback mechanism due to low concentrations of bile and/or pancreatic juice constituents in the duodenal lumen and interference with autoregulating, inhibitory CCK-1 receptors on the I cell.…”
Section: Discussionsupporting
confidence: 53%
“…Because circulating CCK may induce PP release (22)(23)(24), the effect of cholestyramine on PP can at least in part be attributed to the increased CCK release. Similarly, the enhanced pancreaticobiliary response to the amino acid meal with cholestyramine may be explained by the increased plasma CCK levels (18,(25)(26)(27). However, in the present study we also found that cholestyramine tended to increase pancreatic enzyme secretion and significantly stimu lated gallbladder contraction under basal conditions.…”
Section: P W L Thimister Ei Alsupporting
confidence: 44%
“…Chenodeoxycholic acid inhibited CCK release in response to an intraduodenal mixed liquid meal in humans and prevented the enhancement effect of cholestyr amine (3). Administration of CCK receptor antagonists in humans results in a marked exaggeration of meal-stimulated plasma CCK levels (25)(26)(27). Because CCK receptor antago nists inhibit gallbladder contraction to a greater extent than pancreatic enzyme secretion in humans, this suggests that the effect is primarily due to a decreased amount of bile salts in the small bowel (27,32).…”
Section: P W L Thimister Ei Almentioning
confidence: 99%
“…Digestible fat is a powerfu 1 stiinu 1 us for plasma cholecysto kinin (CCK) release and subsequently for gallbladder contrac tion and pancreatic enzyme secretion (11)(12)(13)(14)(15)(16)(17). It has been suggested that the inhibition of gastric acid secretion is also mediated at least in part by CCK (8)(9)(10)(18)(19)(20)(21)(22).…”
Section: Introduction Materialsmentioning
confidence: 99%